Autonomy Italian Style: Sovereignty in Südtirol/Alto Adige: Peer-reviewed article (Italian Review of Legal History, 2022)
A critical legal thinking analysis of autonomy in Südtirol/Alto Adige is useful for rethinking Italian sovereignty in the province. Initiating with articles 5, 6, and 116 of the Italian Constitution (1948) and subsequently with two statutes of autonomy (1948 and 1972) with several amendments, a particular system of law was constructed in the context of the Italian regional state.Several historical events have also determined the current Südtirol/Alto Adige autonomous status. Most notably during the aftermath of World War I, it was subject to a change in sovereignty from Austria to Italy. Soon after, during the fascist period, a failed attempt at so-called Italianization dramatically lessened the rights of the Ladin and German-speaking majority. Moreover, following the devastation of World War II autonomy was granted but not fully accepted in its original form by the majority of the population in Südtirol/Alto Adige. As a consequence, the political movement for self-determination became more relevant and terrorist violence emerged. The international community stepped up to the conflict and the Italian government established a new form of autonomy that brought justice and peace.Thereafter, Südtirol/Alto Adige’s autonomy has received support and recognition from the United Nations, the European Union, and other international organizations.
Keywords: Südtirol/Alto Adige; Autonomy; Sovereignty; Constitutional legal theory; Linguistic minorities